A teaspoon of sugar and a pinch of salt: Reviewing hyperosmolar therapy. Issue 3 (March 2022) - Gilbert, Brian W.; Dingman, J. Spencer; Reeder, Jacob A.; Paola, Sean Di
ABSTRACT: The traditional hyperosmolar agents used to treat patients with elevated intracranial pressure are mannitol and hypertonic sodium chloride solution. This article focuses on some of the pros and cons of these treatments for managing cerebral edema.